A Multidimensional Perspective on Consumer Purchase Decisions: Integrating Event Marketing, Store Atmosphere, and Price in the Restaurant Industry - Khittah Ashilah; Slamet Wijiono; Syarif Hidayatulla; Ach. Faqih Supandi; Bastomi Dani Umbara (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study aims to examine the effects of event marketing, store atmosphere, and price on purchasing decisions at KQ5 Steak and Bowl Jember, both partially and simultaneously. Methodology/approach: This study employed a quantitative descriptive approach. Data were collected through questionnaires and observations involving consumers who attended events organized by KQ5 Steak and Bowl Jember. A non-probability sampling technique was applied, resulting in 120 respondents. Data were analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests. Findings: The results indicate that event marketing, store atmosphere, and price individually influence purchasing decisions. Simultaneously, the three variables have a positive influence on consumers’ purchasing decisions. Practical implications: The findings suggest that restaurant management should strengthen event marketing activities, improve the store atmosphere, and establish appropriate pricing strategies to encourage consumer purchasing decisions. Originality/value: This study integrates event marketing, store atmosphere, and price within a single empirical model to explain purchasing decisions in the restaurant context.